Vitamin C Inhibits Scale Drop Disease Virus Infectivity by Targeting Nrf2 to Reduce Ferroptosis - Jiaming Chen; Yuting Fu; Shaoping Weng; Jianguo He; Chuanfu Dong (Antioxidants)
Scale drop disease virus (SDDV) poses an escalating threat to global aquaculture, prompting an urgent need for research. Our study found that SDDV infection upregulates genes related to iron, oxidative stress, and lipid metabolism, causing iron overload, reactive oxygen species (ROS) accumulation, and ultimately ferroptosis. Among the tested antioxidants, vitamin C (VC) demonstrated the most potent inhibitory effect in mandarin fish, reducing SDDV-induced mortality by 37.5%. qPCR and IFA results showed that VC effectively suppressed SDDV infection; decreased ROS, lipid peroxidation (LPO), and iron levels; and enhanced glutathione peroxidase 4 (GPX4) expression in infected cells. Mechanistically, VC’s inhibitory effect was reversed by the nuclear factor erythroid 2-related factor 2 (Nrf2) inhibitor ML-385, indicating an Nrf2-dependent pathway. VC promoted Nrf2 nuclear translocation and activated downstream antioxidant genes. Moreover, VC modulated inflammation by regulating pro- and anti-inflammatory factors. These findings suggest VC as a promising therapeutic for SDDV infection.